2007
DOI: 10.1364/oe.15.013212
|View full text |Cite
|
Sign up to set email alerts
|

Generation of 1.5 µJ single-cycle terahertz pulses by optical rectification from a large aperture ZnTe crystal

Abstract: We demonstrate the generation muJ-level, single-cycle terahertz pulses by optical rectification from a large-aperture ZnTe single crystal wafer. Energies up to 1.5 muJ per pulse and a spectral range extending to 3 THz were obtained using a 100 Hz Ti:sapphire laser source and a 75-mmdiameter, 0.5-mm-thick, (110) ZnTe crystal, corresponding to an average power of 150 muW and an energy conversion efficiency of 3.1 x 10(-5). We also demonstrate real-time imaging of the focused terahertz beam using a pyroelectric i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
147
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(154 citation statements)
references
References 33 publications
5
147
0
2
Order By: Relevance
“…Fabrication costs are dominated by the substrate price, and we are able to deposit homogeneous layers on substrates with diameters as large as 20 cm (see Methods). Preliminary tests show that driving such large-area trilayers with intense laser pulses easily yields THz pulses with peak fields of several 100 kV cm -1 which exceed those obtained with more strongly pumped large-area ZnTe emitters 50 . Therefore, spintronic THz sources exhibit a high potential for enabling nonlinear-optical studies 51,52 in the difficult-to-access region between 5 and 10 THz.…”
Section: Resultsmentioning
confidence: 97%
“…Fabrication costs are dominated by the substrate price, and we are able to deposit homogeneous layers on substrates with diameters as large as 20 cm (see Methods). Preliminary tests show that driving such large-area trilayers with intense laser pulses easily yields THz pulses with peak fields of several 100 kV cm -1 which exceed those obtained with more strongly pumped large-area ZnTe emitters 50 . Therefore, spintronic THz sources exhibit a high potential for enabling nonlinear-optical studies 51,52 in the difficult-to-access region between 5 and 10 THz.…”
Section: Resultsmentioning
confidence: 97%
“…The main limiting factor in THz generation using ZnTe is free-carrier absorption caused by two-photon absorption of the pump light, which limits pump intensity (see next Section). Even though THz energies as high as 1.5 µJ have been demonstrated by using large pump spots [76] the achieved conversion efficiency of 1.3×10 -5 was rather low. In contrast, by using LN with TPFP, THz energies of 10 µJ [90] and 30 µJ [96] have been reported with pump-to-THz energy conversion efficiencies of 5×10 -4 and 1.1×10 -3 , respectively.…”
Section: 2velocity Matching By Tilting the Pump Pulse Frontmentioning
confidence: 97%
“…4.3). Hence, the useful pump intensity is limited, which is a serious restriction in high-energy THz pulse generation [76]. The situation is similar with GaP, another semiconductor material frequently used for OR with considerably smaller FOM value.…”
Section: 1theory and Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, this detector was used for measuring the energy of near-single-cycle THz pulses with an average frequency of 0.9 THz generated by an accelerator-based source [2]. Afterwards, it was reported that the sensitivity of the Coherent pyroelectric detector at 1 THz was approximately 1.8 times less than the specified sensitivity at 1.06 lm [3], and this difference has been take into account in a following publication [7].Recently, we compared the sensitivity of the Coherent Molectron J4-05 detector with that of another widely used pyroelectric THz detector (Microtech Instruments) [3][4][5][6]. The latter detector is provided with a calibration curve of the spectral dependence of the sensitivity in the frequency range of 0.12-3 THz.…”
mentioning
confidence: 99%